2007
DOI: 10.1364/oe.15.001832
|View full text |Cite
|
Sign up to set email alerts
|

Tunable one-dimensional photonic crystal slabs based on preferential etching of silicon-on-insulator

Abstract: Abstract:We design and assess a one-dimensional photonic crystal slab fabricated by preferential etching of a silicon-on-insulator substrate. The etched grooves are considered to be infiltrated by a highly-birefringent nematic liquid crystalline material. A detailed analysis of the nematic director response within the grooves is presented. We investigate different configurations and demonstrate large band gap shifting when switching the liquid crystal with an applied voltage. Furthermore, we assess this type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In order to further elucidate the nature of the resonance broadening in the measured spectra, we resort to an approximate interpretation based on a weighted average of the simulated spectra. This approach accounts for the observed nonuniformity of the fabricated prismatic element shape due to, for instance, slightly diverse etching rates of the planes exposed in different elements or small variations of the etching angle, which is often found to deviate from the theoretical value of 54.7° during the etching of convex angles …”
Section: Resultsmentioning
confidence: 99%
“…In order to further elucidate the nature of the resonance broadening in the measured spectra, we resort to an approximate interpretation based on a weighted average of the simulated spectra. This approach accounts for the observed nonuniformity of the fabricated prismatic element shape due to, for instance, slightly diverse etching rates of the planes exposed in different elements or small variations of the etching angle, which is often found to deviate from the theoretical value of 54.7° during the etching of convex angles …”
Section: Resultsmentioning
confidence: 99%
“…Only the transverse electric (TE) polarization is considered in the simulation with its electric field in both x and y directions, and magnetic field only in the z direction. The 2-D FDTD [12] and 3-D FDTD [13] studies on the same photonic crystal slab with a defect shows significant difference in output transmission. The discrepancy is mainly due to the 2-D simulation method does not taking into consideration the out-of-plane scattering losses.…”
Section: °Waveguide Designmentioning
confidence: 88%
“…A preliminary theoretical study investigating the optical properties of the corresponding 2D geometry [18] showed that a bandgap effectively appears in such a structure. It has also been described how the bandgap is modified by reorienting the LC infiltrated in the grooves.…”
Section: Introductionmentioning
confidence: 99%